2022
DOI: 10.21883/pss.2022.11.54199.424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect in Gd microwires

Abstract: In Gd microwires obtained by ultrafast cooling of the melt, a change in the magnetic entropy of 12 J/kg K was determined at a Curie temperature of 293 K in a magnetic field of 5 T. This value coincides with the change in the magnetic part of the entropy in bulk single-crystal samples in the same field. It has been found that in a strong magnetic field of 9 T, the temperature dependence of the entropy exhibits two maxima at temperatures of 292 and 312 K. The appearance of an additional entropy maximum in micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…MgO with crystal-lattice orientation (100) was used as a substrate. The gadolinium microwires were produced by extraction of a hanging melt drop followed by superfast cooling on a water-cooled rotating disc [13].…”
Section: Procedures and Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…MgO with crystal-lattice orientation (100) was used as a substrate. The gadolinium microwires were produced by extraction of a hanging melt drop followed by superfast cooling on a water-cooled rotating disc [13].…”
Section: Procedures and Samplesmentioning
confidence: 99%
“…Bulk gadolinium samples have significantly lower crystal anisotropy of magnetization that the anisotropy observed in films and microwires. In [13] authors reported a complicated temperature dependence of magnetic anisotropy found in gadolinium microwires, which contained two maxima of entropy that indicated a complicated-stressed state or a two-phase structure. A considerable MCE can be achieved in nano-and microstructures not only by placing the sample into a magnetic field or switching on the magnetic field, but by varying the permanent magnetic field orientation in relation to the sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Zinc selenide is a direct band gap semiconductor material (E g $ 2.67 eV) displaying strong emission in the blue region of the visible spectrum, 7 which is known to exist in two different polymorphic forms namely, cubic zinc-blende and hexagonal wurtzite, where zinc-blende form is the thermodynamically stable phase. 8 The zinc-blende crystal structure remains stable up to 1,698 K, beyond which it undergoes a structural transformation (3C -2H transformation) into the wurtzite phase. 9 Zinc selenide exhibits both n-type and p-type conduction, characterized by the type of doping resulting from intrinsic defects.…”
Section: Introductionmentioning
confidence: 99%
“…In the family of II–VI selenides, the environmentally friendly compound zinc selenide (ZnSe) is hailed as one of the most promising materials thanks to its extensive applications in the field of optoelectronics 6 . Zinc selenide is a direct band gap semiconductor material (E g ~ 2.67 eV) displaying strong emission in the blue region of the visible spectrum, 7 which is known to exist in two different polymorphic forms namely, cubic zinc‐blende and hexagonal wurtzite, where zinc‐blende form is the thermodynamically stable phase 8 . The zinc‐blende crystal structure remains stable up to 1,698 K, beyond which it undergoes a structural transformation (3C ‐ 2H transformation) into the wurtzite phase 9 .…”
Section: Introductionmentioning
confidence: 99%